2009
DOI: 10.1021/la901145d
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Calcium Oxalates Is Controlled by Molecular Hydrophilicity and Specific Polyanion-Crystal Interactions

Abstract: To gain more insight into protein structure-function relationships that govern ectopic biomineralization processes in kidney stone formation, we have studied the ability of urinary proteins (Tamm-Horsfall protein, osteopontin (OPN), prothrombin fragment 1 (PTF1), bikunin, lysozyme, albumin, fetuin-A), and model compounds (a bikunin fragment, recombinant-, milk-, bone osteopontin, poly-L-aspartic acid (poly asp), poly-L-glutamic acid (poly glu)) in modulating precipitation reactions of kidney stone-related calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 80 publications
5
77
0
Order By: Relevance
“…An affinity of citrate for the {100} face is not surprising as this face is the most Ca 2+ rich [Jung et al, 2004] and the preferred site of interaction for acidic peptides and proteins Langdon et al, 2009]. The predicted interaction of citrate with the {010} face of COM is more surprising as this face is the least preferred by acidic proteins and peptides Taller et al, 2007;Grohe et al, 2009;Langdon et al, 2009]. Also, the SEM and SCIM data reported above indicate that citrate interacts with COM faces in the order {100} 1 {121} 1 {010}.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…An affinity of citrate for the {100} face is not surprising as this face is the most Ca 2+ rich [Jung et al, 2004] and the preferred site of interaction for acidic peptides and proteins Langdon et al, 2009]. The predicted interaction of citrate with the {010} face of COM is more surprising as this face is the least preferred by acidic proteins and peptides Taller et al, 2007;Grohe et al, 2009;Langdon et al, 2009]. Also, the SEM and SCIM data reported above indicate that citrate interacts with COM faces in the order {100} 1 {121} 1 {010}.…”
Section: Discussionmentioning
confidence: 93%
“…In previous studies, we have used confocal microscopy, scanning electron microscopy (SEM) and molecular dynamics (MD) to study interactions between polyelectrolytes and COM crystals Taller, 2007;Grohe et al, 2009;Hunter et al, 2009]. In general, these interactions are dominated by electrostatic forces.…”
mentioning
confidence: 99%
“…The recombinant protein was purified by nickel affinity chromatography and fast protein liquid chromatography. The purified protein was subjected to amino acid analysis and selected samples were analyzed by matrix-assisted laser desorption ionization time-of-flight mass spectrometry, giving a relative molecular mass of 36,100 (26). OPN in which Arg-Gly-Asp (RGD) was mutated to Lys-Ala-Glu (KAE) (OPN-KAE) was prepared using the QuikChange™ Site-directed Mutagenesis System (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…As a result, surface hydrophilicity of S-PLGA scaffold was improved by 26SCS immobilization. It is also reported that scaffold with a hydrophilic surface is more favorable for cell attachment and proliferation [25] as well as the binding of some proteins [32].…”
Section: Morphology Characterizationmentioning
confidence: 99%
“…2B) consisted of three components which were centered at ∼289 eV, ∼287 eV and ∼285 eV and attributed to ester/carboxylic bonds (O C O), ether bonds ( C O ) and carbon-hydrogen bonds ( C H ), respectively [26,32]. Only a slight variation could be seen in chemical bonds groups, indicating aminolysis induced small changes on scaffolds surface (Table S1, supporting information).…”
Section: Xps Analysismentioning
confidence: 99%